Burned Out (IntechOpen, 2025)
Explore the comprehensive examination of stress and burnout in public service with this edited volume, compiled by Dr. Leonard Bright, featuring contributions from esteemed scholars worldwide. This book investigates the underlying causes, repercussions, and mitigation strategies associated with stress in highly demanding and critical professions. The chapters in this book comprise thorough literature reviews that provide extensive overviews of stress and burnout, present empirical research studies that scrutinize how work-related factors influence perceived stress and furnish public servants with easy, actionable exercises and insights to bolster their resilience and well-being in stressful public service occupations. This book is an invaluable resource for public service professionals, researchers, and educators interested in improving their understanding of the art and science of mitigating stress in public service workplaces.